2018
DOI: 10.1039/c8ib00034d
|View full text |Cite
|
Sign up to set email alerts
|

Physical defects in basement membrane-mimicking collagen-IV matrices trigger cellular EMT and invasion

Abstract: In fibrosis and cancer, degradation of basement membrane (BM) and cell invasion are considered as key outcomes of a cellular transformation called epithelial-mesenchymal transition (EMT). Here, we pose a converse question - can preexisting physical defects in the BM matrix cause EMT in normal epithelial cells? On a BM-mimicking matrix of collagen-IV-coated polyacrylamide (PA) gel, we have discovered a reverse phenomenon in which preexisting defects trigger EMT in normal epithelial cells. Through spatiotemporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 64 publications
2
21
0
Order By: Relevance
“…On stiff gels, the vimentin expression increased, and membrane localization of E-cad decreased (Fig. 5C,F,G), both of which are consistent with the stiffness-dependent EMT observed previously (Brown et al, 2013;Nasrollahi and Pathak, 2016;Pathak, 2016;Walter et al, 2018;Wei et al, 2015). On soft gels, longer collagen fibers promoted vimentin expression ( Fig.…”
Section: Upregulated Mechanosensing Markers In Cell Streamssupporting
confidence: 90%
“…On stiff gels, the vimentin expression increased, and membrane localization of E-cad decreased (Fig. 5C,F,G), both of which are consistent with the stiffness-dependent EMT observed previously (Brown et al, 2013;Nasrollahi and Pathak, 2016;Pathak, 2016;Walter et al, 2018;Wei et al, 2015). On soft gels, longer collagen fibers promoted vimentin expression ( Fig.…”
Section: Upregulated Mechanosensing Markers In Cell Streamssupporting
confidence: 90%
“…A hallmark of EMT is the loss of epithelial polarization, which by itself is linked to anchorage of epithelial layers on a basement membrane (BM). Walter et al found that defects in the BM and of Col IV deposition in particular can trigger EMT (Walter et al, 2018). In proximal tubular epithelial cells, Col IV helps to maintain an epithelial phenotype, while Col I promotes EMT (Zeisberg et al, 2001).…”
Section: The Ecm Regulates Emt and Metastasismentioning
confidence: 99%
“…The increased motility/invasiveness associated with the mesenchymal cell state has linked the EMT program with metastasis, in which cell separation from the primary tumor mass can be considered as the rst step of the invasion-metastasis cascade. Thus, a variety of studies have demonstrated that induction of an EMT program allows carcinoma cells to lose cell-cell junctions, degrade local basement membrane via elevated expression of various matrixdegrading enzymes, and thus support their migration and invasion [21][22][23][24]. Therefore, SIPA1L3 overexpression promotes malignant lung cell growth, invasion, and EMT, which may explain our ndings that SIPA1L3 overexpression was the major de ning characteristic of NSCLC tumors and correlated with several clinicopathological factors.…”
Section: Discussionmentioning
confidence: 59%